COGNITIVE OUTCOMES IN CHILDREN WITH CONDITIONS AFFECTING THE SMALL INTESTINE : A SYSTEMATIC REVIEW - Ratu Alicia, Dea Nabila (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
It is possible that children who suffer from gastrointestinal (GI) disorders have a less-than-ideal nutritional status, particularly as a result of malabsorption and symptoms that are brought on by a restricted food intake. A cognitive function is any conscious mental action, including thinking, remembering, learning, or utilizing language. Examples of cognitive functions include these. Attention, memory, consideration, the ability to solve problems, and executive abilities such as planning, assessing, supervising, and evaluating are all aspects of cognitive function. Neurodevelopment issues in intestinal failure (IF) children have surfaced. The researchers Hukkinen et al. reviewed the existing research and came to the conclusion that children with IF are at a high risk of delayed psychomotor and cognitive development. However, this conclusion was drawn from a small number of studies that used a variety of research methods. This study reveals that children with IF and surgical NEC are at a greater risk of having bad cognitive outcomes in patients with illnesses affecting the small intestine who require PN. These patients include individuals with conditions such as Crohn's disease and ulcerative colitis.